Elucidation of electric characteristics for P and N type polycrystalline silicon vertical thin film transistors. (8th December 2022) - Zhang, Peng; Jacques, Emmanuel; Rogel, Régis; Pichon, Laurent; Bonnaud, Olivier
Abstract: P and N type polycrystalline silicon has been applied in thin film transistors (TFTs) for driving a range of displays, and for building up complementary metal oxide semiconductor (CMOS)-like circuits. In one aspect, the high driving current is required, which is usually achieved by improving field effect mobility of the active layer. For another, balanced electrical characteristics are required for achieving CMOS-like logic circuits. In this article, in order to increase driving current, P and N type polycrystalline silicon vertical TFTs configuration is proposed that can get rid of the strict requirement of the field effect mobility in order to increase the driving current. In addition, the balanced electrical properties are demonstrated for P and N type vertical TFTs, which are elucidated by the density of states calculations. The simple Simulation Program with Integrated Circuit Emphasis (SPICE) modelling indicates the potential application in CMOS inverter based on our vertical TFTs.